At the end: A vignette-based investigation of strategies for managing end-of-life decisions in the intensive care unit. (November 2021) - Reader, Tom W; Dayal, Ria; Brett, Stephen J
Background: Decision-making on end-of-life is an inevitable, yet highly complex, aspect of intensive care decision-making. End-of-life decisions can be challenging both in terms of clinical judgement and social interaction with families, and these two processes often become intertwined. This is especially apparent at times when clinicians are required to seek the views of surrogate decision makers (i.e., family members) when considering palliative care. Methods: Using a vignette-based interview methodology, we explored how interactions with family members influence end-of-life decisions by intensive care unit clinicians ( n = 24), and identified strategies for reaching consensus with families during this highly emotional phase of care. Results: We found that the enactment of end-of-life decisions were reported as being affected by a form of loss aversion, whereby concerns over the consequences of not reaching a consensus with families weighed heavily in the minds of clinicians. Fear of conflict with families tended to arise from anticipated unrealistic family expectations of care, family normalization of patient incapacity, and belief systems that prohibit end-of-life decision-making. Conclusions: To support decision makers in reaching consensus, various strategies for effective, coherent, and targeted communication (e.g., on patient deterioration and limits of clinical treatment) were suggested as ways to effectively consult with families on end-of-life decision-making.